(untitled) (Research, Society and Development, 2022)
Introduction: Diseases that affect the respiratory tract are acute or chronic and have one of the highest mortality rates in the world, directly affecting millions of people of all ages. Pneumonia is described as a disease known since the dawn of humanity, found in ancient Greek, Roman and Arabic writings. Knowledge of microbial activity in pneumonia and Streptococcus as the causative agent was discovered about 120 years ago. Methods: This is an integrative review, which presents as a guiding question the existence of evidence on the high number of children hospitalized in pediatric units with viral pneumonia, with the outcome of enabling better guidance in preventive care. Results and discussion: The findings highlight the need to carry out education with the legal guardians of children, since this public, for presenting greater awareness of vulnerability to pneumonia. Conclusion: The viruses that trigger viral pneumonia are responsible for flu and colds, such as Influenza A, B or C, H5N1, H1N1 and even the new coronavirus COVID-19.